2021
DOI: 10.3390/membranes11090701
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on a Ceramic Membrane Condenser with Air Medium for Water and Waste Heat Recovery from Flue Gas

Abstract: Ceramic membrane condensers that are used for water and waste heat recovery from flue gas have the dual effects of saving water resources and improving energy efficiency. However, most ceramic membrane condensers use water as the cooling medium, which can obtain a higher water recovery flux, but the waste heat temperature is lower, which is difficult to use. This paper proposes to use the secondary boiler air as the cooling medium, build a ceramic membrane condenser with negative pressure air to recover water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The purge gas relative humidity is stable within the range of 90–100%. In contrast, the purge gas relative humidity was higher than 100% in the literature . The reason is that the purge gas has a negative pressure in the literature, while the purge gas has a positive pressure in this paper.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The purge gas relative humidity is stable within the range of 90–100%. In contrast, the purge gas relative humidity was higher than 100% in the literature . The reason is that the purge gas has a negative pressure in the literature, while the purge gas has a positive pressure in this paper.…”
Section: Resultsmentioning
confidence: 58%
“…It can be found that the 0.4 nm ceramic membrane water recovery rate and efficiency are far lower than the other ceramic membranes' water recovery rate and efficiency. In the literature, 43 negative-pressure air is used as the cooling medium, and the 0.4 nm ceramic membrane water recovery characteristics are also similarly poor. The 0.4 nm ceramic membrane is not suitable for the flue gas dehydration process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During waste heat recovery, the heat is recovered to the unit's regenerative system to squeeze out a part of the extraction steam, which will increase the cooling source loss of the steam turbine and reduce the thermal efficiency of the unit. However, after the waste heat of flue gas is recovered, the increase of power generation is realized, which is based on the constant fuel quantity of the unit, so the total thermal economy is increased [41].…”
Section: Equivalent Enthalpy Drop Methodsmentioning
confidence: 99%
“…The process of food production is energy-intensive because it requires evaporating, which make heat recovering from the condenser flow economically and energy-efficient (Oosthuizen et al, 2020). In the industrial boilers, the waste heat is successfully recyled to recover latent heat from the exhaust gas to achieve greater efficiency and fewer emissions than traditional boilers (Lee et al, 2015;Men et al, 2021;Teng et al, 2021;Wang et al, 2012;Xu et al, 2013), however, the condensing water temperature must be lower than the flue gas temperature in the condensing boiler and the more reasonable heat exchange regime will be achieved by the lower waste heat recovery temperature (Abdelaziz et al, 2011a;Atabani and Saidur, 2012;BEE, 2009;Han et al, 2021;Huang et al, 2017). Understanding of energy efficiency is important to improve industrial boiler and reduce energy losses and costs in the sugar production and drying industry (Jafarkazemi et al, 2016;Kanoglu et al, 2007;Khalid et al, 2015;Tolga Taner, 2015;Tolga Taner and Sivrioglu, 2015).…”
Section: Introductionmentioning
confidence: 99%